Symbouki: a meta‐analysis on the emergence of sound symbolism in early language acquisition. Issue 5 (15th March 2018) - Fort, Mathilde; Lammertink, Imme; Peperkamp, Sharon; Guevara‐Rukoz, Adriana; Fikkert, Paula; Tsuji, Sho
Abstract: Adults and toddlers systematically associate pseudowords such as "bouba" and "kiki" with round and spiky shapes, respectively, a sound symbolic phenomenon known as the "bouba‐kiki effect". To date, whether this sound symbolic effect is a property of the infant brain present at birth or is a learned aspect of language perception remains unknown. Yet, solving this question is fundamental for our understanding of early language acquisition. Indeed, an early sensitivity to such sound symbolic associations could provide a powerful mechanism for language learning, playing a bootstrapping role in the establishment of novel sound–meaning associations. The aim of the present meta‐analysis (SymBouKi) is to provide a quantitative overview of the emergence of the bouba‐kiki effect in infancy and early childhood. It allows a high‐powered assessment of the true sound symbolic effect size by pooling over the entire set of 11 extant studies (six published, five unpublished), entailing data from 425 participants between 4 and 38 months of age. The quantitative data provide statistical support for a moderate, but significant, sound symbolic effect. Further analysis found a greater sensitivity to sound symbolism for bouba‐type pseudowords (i.e., round sound‐shape correspondences) than for kiki‐type pseudowords (i.e., spiky sound‐shape correspondences). For the kiki‐type pseudowords, the effect emerged with age. Such discrepancy challenges the view that sensitivity to sound symbolism is an innate language mechanism rooted in an exuberant interconnected brain. We propose alternative hypotheses where both innate and learned mechanisms are at play in the emergence of sensitivity to sound symbolic relationships. Abstract : Our meta‐analysis shows a moderate, but significant sensitivity to sound‐symbolism in early language learning with greater sensitivity to bouba‐type than to kiki‐type pseudowords, with the latter emerging with age.